The Political Role of Political Parties in Egypt After 2014: Mostaqbal Watan ‘The Nation’s Future Party’ is a Case Study - Abdul Rasoul, Osama Faik; Hussein Jaafar, Shubbar; Ali Hussein, Hussein (JOM, 2024)
Political parties are a fundamental kind of formal political associations andone of their most significant manifestations. The effectiveness of theseparties contributes to the institutionalization of the system as they serveas a conduit for communication between the authority and individuals.The most important functions of these parties are represented inparticipation, political education, and recruitment. These parties alsobasically represent a group of people that share beliefs, such as a shareddestiny and unity of purpose. They strive to achieve the function bygaining political power or, at least, by influencing state publicpolicymaking. Furthermore, the beginning of political associations in Egyptdates to secret associations at the end of the 1960s of the 19th centuries.Some sources indicated the existence of some secret societies in Al-Azhar, in addition to other associations, at the end of the 1970s. As thecrisis deteriorated in society, which led to a sense of how bad the countryconditions had become, three political powers emerged: the army,intellectuals, notables and scholars, and members of the Shura Council ofRepresentatives, which were represented by the political organizationsthat were formed in that period, reflecting popular hopes for reform andprogress. To begin with, it can be said that the emergence of MostaqbalWatan ‘The Nation’s Future Party’ was not very different from theemergence of several political parties that emerged after the January 25Revolution, all of them were characterized by superiority and elitism.Thus, it was more elitist and superior to a natural emergence among agroup of stakeholders that share at least an ideology or political referencewith each other. Accordingly, it can be said that founding the party camein transitional circumstances, following the June 30 Revolution, when agroup of young people from the Egyptian Student Union carried out ayouth campaign entitled (The Nation’s Future). The main goal of this partywas to pass the 2014 constitution, but some quickly embraced the ideaand worked to transform it into a political party. This caused a greatuproar about the method of establishment and who was behind the party.